The Man from Utah = [El hombre de Utah] - Bradbury, Robert N. (Robert North); Parsons, Lindsley, 1905-1992; Wayne, John, 1907-1979; Young, Polly Ann, 1908-1997; Lone Star Productions; Cinetel Films ([Los Angeles, CA] : Lone Star Productions, 1934)
Crooked promoters use a rodeo to swindle unsuspecting cowboys. John Wayne, as a lawman, goes undercover to capture these vermin.
Originally released as a motion picture in 1934.
"A Paul Malvern production."
John Wayne, Polly Ann Young, Anita Campillo, Edward Peil, George Hayes, Yakima Canutt, George Cleveland.
Cinematographer, Archie Stout; editor, Carl Pierson.
Dubbed into Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: Rodeos -- Drama; West (U.S.) -- History -- Drama; Western films; Feature films; Internet videos; Short films; Streaming video